Some Facts Bearing on the Silver Program - Berridge, William A. (The Review of Economics and Statistics, 1934)
THIS companion article to that on gold, in th( July REviEw,' does not attempt to revie; the silver program in the light of either economi history or economic theory and particularly not in reference to the validity of that prograir as a matter of economic and other policy. Thos( aspects have already been ably presented elsewhere by such writers as Leong, Kemmerer, Graham, Leavens, G. A. Smith, and various others. Rather, the purpose is simply to present a condensed summary of factual, and especially statistical, data bearing upon the silver program. Special attention is devoted to the question ol how much progress toward the objectives of that program has been realized. The leading steps in legislative enactment, and in administrative action thereunder, are treated in a logical rather than the strict chronological order. Certain indirect or implied objectives are given little or no consideration; those reviewed are the ones to which main emphasis has been given in the announced statements of purpose, and are considered under four heads: (I) Metallic monetary reserves; (2) Price; (3) Production; (4) China.